Microstructure evolution, texture development, and mechanical properties of hot-rolled 5052 aluminum alloy followed by annealing - Jianxin Wu; Faramarz Djavanroodi; Ceren Gode; Mahmoud Ebrahimi; Shokouh Attarilar (Materials Research Express, 2022)
Aluminum alloys, especially the 5000 series, have drawn the attention of the transportation industry due to their lightweight and consequently reduced fuel consumption. In this regard, one of the major problems of this alloy is its low strength and ductility that can be solved using rolling and post-annealing. Accordingly, the present study concentrates on this issue. Microstructural images showed that the rolling process develops a lot of tangled and trapped dislocations in the sample, which gradually lead to the formation of dislocation bundles and networks. Subsequent annealing can produce a more homogeneous structure with clear grain boundaries and low dislocation density in the inner region of the grains. However, grain refinement efficiency through rolling is retained even after annealing. Initial and rolled Al5052 with the maximum intensity of 2.87 and 6.33 possess the lowest and highest overall texture. Also, post-annealing decreases the texture intensity to 6.33 and 4.87 at 150 and 200 °C, respectively. In this context, deformation texture components strengthen considerably after the rolling process due to the formation of shear bands, and they slightly weaken during heat treatment. Although the initial annealing of the as-received material does not cause discontinuous recrystallization during rolling, it may facilitate the material recovery before rolling. Post-annealing was found to decrease the improved effect of strength by rolling and increase the negative influence of ductility due to the inhibition of dislocation strengthening. The results showed that both dislocation density and the precipitation of Mg atoms are influential for electrical resistivity.